Family psychoeducation with caregivers of schizophrenia patients: Impact on perceived quality of life - Pankaj Kumar Verma (Industrial Psychiatry Journal, 2019)
Background: Schizophrenia is a devastating and chronic mental illness. Considering the nature of illness along with routine psychiatric care, various supportive therapies are recommended. Family psychoeducational approach has been developed to increase patients' as well as their caregivers' knowledge and insight into their illness. It is postulated that this increased knowledge and insight will enable people with schizophrenia and their caregivers to cope in a more effective way with the consequences of their illness, thereby improving prognosis. Aim: The aim of this study is to assess the efficacy of family psychoeducation intervention on the caregivers of schizophrenia patients with respect to their perceived quality of life. Materials and Methods: A total of 30 caregivers of male schizophrenia patients were selected through purposive sampling technique. Patients were divided into two groups, namely, experimental and control group. Family psychoeducation intervention was given on twice-monthly basis for 6 months to the experimental group caregivers. Baseline assessment was carried out with the help of WHO Quality of Life-BREF followed by intervention and then posttherapeutic assessment was done with same tool. Results: Most of the caregivers were above 40 years of age group, married, and male. Following family psychoeducation, significant improvement in overall quality of life scores was observed in experimental group caregivers compared to control group caregivers where no such intervention was provided. Conclusion: Family psychoeducation is feasible and useful in our clinical population.